PENANGANAN KELUHAN TAMU PADA ROOM SERVICE FOX HOTEL PEKANBARU - Saragih, Tiwi Ravika; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the handling of guest complaints at Fox Hotel Pekanbaru Room Service. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are the Food and Beverage Manager, Food and Beverage Supervisor and Room Service employees. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded. aspects of Handling Guest Complaints in Room Service are in line with standard operational procedures listed in the hotel itself. This dissatisfaction comes from the poor service or facilities available at the Room Service. In accordance with the types or categories of existing complaints, complaints at Room Service Fox Hotel Pekanbaru are mostly found in the form of Mechanical Complaints, Atitudinal Complaints, Service - Related Complaints and Unusual complaints. Many guests complain about the lack of friendliness of waiters and waitresses in Room Service or the lack of hospitality of waiters and waitresses, such as not smiling and rarely greeting guests. Then regarding the lack of facilities and infrastructure in Operational Room Service, food is given too late during in-room delivery, it takes too long to deliver food to room service and the food served is not appropriate. Keywords: Complaints, Room Service, Fox Hotel